O crescimento dos fundos de investimentos no Brasil, no período pós-plano Real, e sua importância para economia nacional - Oliveira, Sérgio Luiz Cordeiro de (2006)
This work presents, a research, with focus in the analysis of the evolution of the industry of investment fund in Brazil, and its importance for national economy. With the implantation of the Real Plan, (Plan of Economic Stability), in 1994, the Brazilian economic scene moved drastically, it was transferred to coexist it a relative monetary stability, and as consequence, the national financial system started to coexist: reduced edges of yield, with the nip of the market, with the entrance of international banks, the elimination of the inflationary profits and the sprouting and sophistication of financial instruments. In this new economic scene, new demands for the financial market had appeared, and were to leave of this moment that the industry of investment fund, grew and was consolidated, presenting the biggest evolution and development, amongst the products of banking captation. This industry manages a patrimony superior the R$ 650 billion, (jul/2005), equivalent about 42% of the Brazilian GIP and gains each time more importance in the national economy, as instrument of saving the disposal of significant parcel of the population, and as supplier of resources for the productive sector and the government in the financing and allonge of the public debt of the country. In the characterization of the research one searchs to context the evolution of the industry of the investment funds to the long one of last the 11 years (1994 - 2004), and the form that this type of financial investment evolved and was developed in the Brazilian financial market. The case study also it searchs to tell to the impacts and trends of this segment, and its importance for national economy, over all in the financing of the Brazilian Public Debt.